Manifestações patológicas em áreas molháveis em alvenaria e gesso acartonado em edifícios hotéis - Francescatto, Taciane Roberta (2019)
Buildings that use the drywall system for internal partitioning need more care in environments with high moisture content, because the plasterboard component is sensitive to water action. Due to its application in the commercial sector and especially in the hotel sector, it is common to use plasterboard in wettable environments. Thus, there is a dichotomy between these environments and the sealing component. Thus, this research aims to present and analyze the pathological problems that occur in wettable environments of hotel buildings built with masonry walls and plasterboard. Regarding the recommendations proposed by the technical literature for the construction of plasterboard walls in wettable environments, the bibliographic research identified different constructive guidelines among the analyzed documents and, however, all are guided by NBR 15758-1 (2009), which is complemented by executive technical details provided by the manufacturers manuals. To identify the main pathological manifestations that occur in wettable environments built with drywall, a field survey was conducted involving hotels in the region of São Carlos-SP. In all, 7 hotels participated in the qualitative research through the application of quizzes, and among these, 3 participated in the quantitative research, developed from the analysis of documents of daily occurrences provided by the participants of this study. Regarding the results obtained from the application of the quizzes, it was possible to know the constructive profile of the buildings and maintenance teams of the hotel sector. Among the findings, it was found that most of the projects are built with reinforced concrete structure and masonry, with few using the drywall system for internal sealing, and in general, few have a building sector. self-maintenance and assiduous, it was found a unique responsibility, in which the team includes only one employee who is responsible for the management and for small and medium repairs. Regarding the documentary analysis, in Hotel 01 (EH1) and EH2, both with drywall, the area with the highest incidence of problems was the bathrooms, with 54% and 52% of occurrences, respectively. Already the EH3, with walls in masonry, the bedroom zone was the one with the highest number of records, with 65% of occurrences and 27% in bathrooms. Regarding the occurrences, although EH3 presents more records numerically, no significant differences were found when comparing the problems that occur in drywall seals with those in masonry. In the three hotels, the place with the most occurrence was in the sanitary installations, with 80% of the records, of which 48% refer to the detachment of objects from the wall. Finally, this research identified a set of pathological manifestations, with their characteristics and influences in the drywall system. This research was of great value and contributes to the knowledge of the real problems that occur in hotel buildings, because it is from records of occurrences that it is possible to raise more reliable studies regarding the pathological manifestations. This study has great potential to expand the knowledge of pathology in other types of buildings.